Literacy Development Through Reading Aloud Activities for the Community of Winduraja Village, Kawali Subdistrict, Ciamis Regency - Putri, Adelia Riani; Mira Dwi Kuswandani; Arie Budiawan; Kiki Endah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This Community Service Program (PKM) aims to improve literacy among the residents of Winduraja Village, Kawali Subdistrict, Ciamis Regency through training in reading aloud for PKK cadres and parents of MIS Winduraja students. A descriptive qualitative method was used, with data collection techniques including observation, interviews, and documentation. The activity was conducted at the Gada Membaca Winduraja Community from July 30 to August 12, 2025, and included presentations on reading aloud techniques, hands-on practice, and interactive discussions. The results of the activity showed that the reading aloud method was effective in increasing reading interest, enriching vocabulary, and strengthening the emotional bond between readers and listeners. PKK cadres and parents acquired skills in vocalization, intonation, and selecting appropriate reading materials, enabling them to become literacy facilitators within families and communities. The long-term implication is the creation of a sustainable family- and community-based literacy ecosystem in Winduraja Village. Keywords: Literacy, Reading Aloud, PKK Cadres, Parents